DETERMINAN TRANSPARANSI INFORMASI KEUANGAN DAERAH MELALUI E- GOVERNMENT PEMERINTAH DAERAH DI SUMATERA SELATAN - Verawaty Verawaty (Universitas Muhammadiyah Metro, 2017)
ABSTRACT The purpose of this study was to analyze the association of Local Own Source Revenue, General Allocation Fund, Special Allocation Fund, and Debt Ratio as the determinants of the Local Government Financial Information Transparency. The population was all local government in South Sumatra. The statistical results showed that only Local Own Source Revenue showed the positive association to Financial Information Transparency. The study implication recommends that the local government must improve the implementation of e-government in order to enhance accounting transparency that they present in the website.